Effects of Coffee Consumption on Acne Vulgaris Severity in Atma Jaya Medical Students in Jakarta, Indonesia - Natasha, Tiffanie; Wijaya, Lorettha; Djuartina, Tena; Arieselia, Zita (School of Medicine and Health Sciences, Atma Jaya Catholic University of Indonesia, 2024)
Introduction: Acne vulgaris is a common multifactorial skin disease. With diet as one of the possible factors, the rising habit of coffee consumption may have its own effects on acne. In present time, there is a lack of study between coffee consumption and acne vulgaris as well as the relationship between the two topics. This study aimed to analyze the effects of coffee consumption on acne severity. Methods: A cross-sectional study was conducted from September to December 2022 on 106 Atma Jaya medical students in Jakarta, Indonesia, who has acne and consumed coffee in the past month when the study was performed. The students were asked to fill a questionnaire about demographic and filtering questions along with questions about coffee consumption in the past month based on Diet History Questionnaire III (DHQ III). Acne lesion observations on the face, upper back, and chest were then performed on every individual to calculate acne severity based on Global Acne Grading System (GAGS). Results: Students who only drank black coffee tend to have lower acne severity score (mean±SD: 19.69±5.68) than those who drank coffee mixtures beverages (mean±SD: 25.41±5.11) (p-value<0.001). There was a significant negative correlation between acne severity scores and amount of black coffee consumed (p-value=0.001). On the other hand, there was a significant positive correlation between acne severity scores and amount of coffee mixtures beverages consumed (p-value<0.001). Conclusion: The results of this study show that the types and amount of coffee consumed had significant effects on acne vulgaris severity in medical students. Keywords: acne vulgaris - black coffee - coffee mixtures